إمكانية استخدام الرش العامودي في الزراعة المحمية ( في ظروف الساحل السوري ) - مخول, عدنان مخائيل (Latakia University Journal -Biological Sciences Series, 2013)
يهدف البحث لحماية العاملين في مجال الزراعة المحميّة من التعرض المباشر لرذاذ المبيد . يستخدم الرش العامودي لرش المبيدات الزراعية ، والسوائل الأخرى بين صفوف الأشجار المثمرة والكروم والخضار وفي الزراعة المحميّة في الدول المتقدمة زراعياً، إذ تسمح البنية الهيكلية للبيوت الزراعية، وتنظيم العمليات فيها بدخول عربة متخصصة برش المبيدات مزودة بذراع رش عمودي، ولكن الزراعة المحمية في الساحل السوري لم تتوفر لها الظروف المناسبة لمكننة عملية رش المبيدات، وخاصة مسار أرضي مناسب لتحريك ذراع رش على عربة ، ونتيجة البحث والتجريب (2012 – 2009 ) ، تم ابتكار نموذج جديد لجهاز رش مبيدات آلي ، يتحرك فيه ذراع رش عمودي على سلك بسرعة ( 18 – 45 [m/min] ) بتحكم آلي ، وبمعدل تصريف للمبعثرات ( 2.81 [L/min ) ، النتائج التجريبية لتوزيع قُطيرات سائل المبيد ( 51 )] قُطيرة / cm2 [ بمتوسط قطر( 70 [microns] ) على السطح العلوي للورقة، و( 43 ) قُطيرة بقطر ( 40 [microns] ) على السطح السفلي للورقة، سيتم متابعة الدراسة بهدف تحسين المواصفات الفنية للجهاز الجديد ، والتقليل من تكاليف إنتاجه، واستخدامه . The research aims to protect greenhouse farmers from direct exposure to pesticide spray. A vertical spray boom is used among the vineyards, orchards and vegetables, as well as in greenhouses in agriculturally developed countries where the structure and organization of agricultural operations permit fumimatic motor–driven sprayers and manual-driven trolley sprayers. Greenhouses on the Syrian Coast, however, do not meet the appropriate conditions for automating the spraying process; In particular there is no path paved ground to fit the movement of the sprayer. As a result of research and experimentation (2009-2012), a new version of the vertical spray boom was invented. The device moves on a cable with a speed equal to (18–45m/min) and an average precipitation of (2.81L/min). The results indicate that the number of droplets is (51/cm2) with a medium diameter of (70 microns) on the upper surface, and (43/cm2) (40 microns) on the lower surface. A subsequent study will be conducted to improve the technical specifications of the new sprayer, and reduce manufacturing costs and usage.